NE GOSIA SI PE NGA DA A N T A NA H UNT UK NOR MA L ISA SI DA E R A H A L IR A N SUNGA I (DA S) BE R INGIN K OT A SE MA R A NG - sheila eka soraya; yuwanto .; dzunuwanus ghulam manar (Journal of Politic and Government Studies, 2016)
A BST R A C TLand Acquisition process in construction of development for public ingeneral will be full of problems or conflictual. This is due to sensitive of soil and landavailability is limited. However, Land Acquisition in Mangkang Wetan and MangunharjoVillage, Semarang, land acquisition carried out for normalization of DAS is almost nosignificant conflict . This is an interesting process of land acquisition to normalize DASBeringin in Semarang. This research used a qualitative approach with descriptive type.This research is composed to construct or reportray land acquisition process fornormalization of DAS Beringin in Semarang. The process was executed smoothly as aneffort to overcome flooding that occurs in Mangkang Wetan village and Mangunharjovillage of Tugu District, Semarang. Researchs found the mechanism of land acquisition,source of funds, constraints, solutions, and factors that support the achievement of thenegotiations. Based on the results of research, concluded that the implementation of landacquisition in normalization negotiations DAS Beringin has been proceed seamlessly,without any meaningful constraints. There were 136 plots of land belonging to residentshad freed by the government.Researcher suggest, necessity for improving handling in the following up theprocesses of land acquisition, the physical development, considering that every year theMangkang Wetan village and Mangunharjo village is affected by floods, especiallyduring heavy rainfall in the rainy season. Research on the negotiation process of landacquisition in the context of normalization DAS Beringin can be used as an example ofsuccessful land acquisition activities because it is easily reached an agreement betweenthe government and the citizens, particularly in dealing with similar problems, namelycope with floods that might occur on other watersheds in the city, even in all regions inIndonesia.K eyword : L and A cquisition, normalization of DA S Beringin.